Design A Prototype of Temperature Logging Tools for Geothermal Prospecting Areas - Supriyanto, Supriyanto; Mahmudah, Rizki; Marwah, Nella (UI Scholars Hub, 2013)
The costs of geothermal exploration are very high because technology is still imported from other countries. The local business players in the geothermal sector do not have the ability to compete with global companies. To reduce costs, we need to develop our own equipment with competitive prices. Here in Indonesia, we have started to design a prototype of temperature logging tools for geothermal prospecting areas. This equipment can be used to detect temperature versus depth variations. To measure the thermal gradient, the platinum resistor temperature sensor is moved slowly down along the borehole. The displacement along the borehole is measured by a rotary encoder. This system is controlled by a 16-bit H8/3069F microcontroller. The acquired temperature data is displayed on a PC monitor using a Python Graphical User Interface. The system has been already tested in the Gunung Pancar geothermal prospect area in Bogor.